The Determinants Factors of Biogas Technology Adoption in Cattle Farming: Evidences from Pati, Indonesia - Wahyudi, Jatmiko (Center of Biomass & Renewable Energy, Diponegoro University, 2017)
Even though biogas technology has been introduced in Indonesia since 1990â€™s and having the potential, the rate of biogas adoption in Indonesia runs slowly. It is important to understand factors encouraging or discouraging potential adopters to build biogas plant. The development of livestock sector especially cattle farming in Indonesia can be seen as the opportunity to increase the rate of biogas adoption. This study investigated the factors affecting households of cattle farmer to adopt or not to adopt biogas technology. A cross-sectional research survey was carried out by using structured questionnaires as the primary tool to collect data from both biogas adopters and non biogas adopters in Pati regency, Indonesia. Socioeconomic characteristic of potential biogas adopters plays an important role to ensure the adoption of biogas technology sustainable. Socioeconomic characteristic regarding having high social status determines individual to adopt biogas relatively earlier than other members of a social system. Having high income and education enables traditional farmers to finance biogas plant by their own money or access aid from the government or other agencies. Among other attributes of innovation, relative advantage of installing biogas plant is the most determinant attribute to speed the rate of biogas adoption. Having biogas plant was perceived as better option and generated more benefits compared to previous technology or method.Article History: Received May 17th 2017; Received in revised form August 5thÂ 2017; Accepted Sept 6th 2017; Available onlineHow to Cite This Article: Wahyudi, J. (2017) The Determinant Factors of Biogas Technology Adoption in Cattle Farming: Evidences from Pati, Indonesia, Int. Journal of Renewable Energy Development, 6(3), 235-240.https://doi.org/10.14710/ijred.6.3.235-240